2018
DOI: 10.3390/nano8030143
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Coated Zinc Oxide Nanoparticles as Innovative ROS-Generators for Photodynamic Therapy in Cancer Cells

Abstract: In the present paper, we use zinc oxide nanoparticles under the excitation of ultraviolet (UV) light for the generation of Reactive Oxygen Species (ROS), with the aim of further using these species for fighting cancer cells in vitro. Owing to the difficulties in obtaining highly dispersed nanoparticles (NPs) in biological media, we propose their coating with a double-lipidic layer and we evaluate their colloidal stability in comparison to the pristine zinc oxide NPs. Then, using Electron Paramagnetic Resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 34 publications
3
82
0
Order By: Relevance
“…The surfaces of pristine ZnO NPs contain many neutral hydroxyl groups, which govern the surface charge behavior of nanomaterials [20]. The stability of ZnO nanocrystal colloids is also affected by charge and surface chemistry, which are important for the interaction between inorganic nanoparticles and organic organisms [21]. HeLa cells usually possess a high negative membrane potential due to anionic phospholipids or other charged proteins and other active substances.…”
Section: Introductionmentioning
confidence: 99%
“…The surfaces of pristine ZnO NPs contain many neutral hydroxyl groups, which govern the surface charge behavior of nanomaterials [20]. The stability of ZnO nanocrystal colloids is also affected by charge and surface chemistry, which are important for the interaction between inorganic nanoparticles and organic organisms [21]. HeLa cells usually possess a high negative membrane potential due to anionic phospholipids or other charged proteins and other active substances.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this mechanism is photodynamic therapy (PDT) (Dabrowski, 2017). We have previously (Ancona et al, 2018) proposed the use of hybrid nanoparticles, able to produce intracellular ROS only when remotely activated by UV light irradiation. The photogeneration of electrons (e − ) and holes (h + ) have the ability to react with the environment forming superoxide radical anions (O 2− ) when e − reduce oxygen molecules while hydroxyl radicals (HO‱) and hydrogen peroxide (H 2 O 2 ) molecules are produced when h + oxidize water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…PDT has been employed with promising results for the treatment of bladder, esophagus, skin, and others cancers, and is at the stage of clinical evaluation (van Straten et al, 2017). A possibility, is to combine the use of ZnO with UV in a novel PDT approach: ZnO nanoparticles have been actually employed as carrier of a photosensitizer and other chemotherapeutics (Zhang et al, 2011;Firdous, 2018) or directly as photosensitizer, as we reported recently (Ancona et al, 2018), generating superoxide, hydrogen peroxide, and hydroxyl radicals and decreasing HeLa cells viability upon irradiation. However, the main limitation of PDT is the poor tissue penetration of light, in particular the UV, that limits PDT for the treatment of superficial tumors, as melanomas.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer systems are a challenging area of study because of the properties concerning the polymer chain lengths, as well as the different conformations they assume depending on the environment. More specifically, polymer self-assembly in solution (of particular interest due to numerous applications [41][42][43] ) is still a challenge from a simulation point of view due to the subtle effects that solvents and temperature have on the polymer conformation. Particularly important is the understanding of the polymer chain behaviour in "good" and "bad" solvents and a mixture of them.…”
Section: Introductionmentioning
confidence: 99%